CORPORATE GOVERNANCE AND STOCK MARKET REACTION TO SEASONED EQUITY OFFERING ANNOUNCEMENT BY FIRMS IN NIGERIA (Malaysian Management Journal, 2021)
This study examined the effect of corporate governance variables of board independence, institutional ownership, managerial ownership, board size, and director expertise on the market reaction to seasoned equity offering (SEO) announcements by firms in the Nigerian stock market. The event study methodology was employed, and abnormal returns were computed using the market model. A total of 62 announcements by 38 firms listed on the Nigerian stock exchange from 1st January 2006 to 31st December 2016 were included in the analysis. The study recorded significant positive cumulative abnormal returns before and after the announcement day, and a significant negative cumulative abnormal return upon the announcement day of SEOs. Similarly, significant positive cumulative abnormal returns were recorded six months before the SEO announcement day and negative significant cumulative abnormal returns six, twelve, and twenty-four months after the announcements. Furthermore, there were significant cumulative abnormal returns upon SEO announcements for all the proxies of corporate governance assessed by the study. The implication of the findings of negative significant cumulative abnormal returns on the day of the announcement and beyond was consistent with previous arguments that firms issuing SEOs earn negative abnormal returns on the day of the announcement was the result of the information asymmetry between managers and investors. By contrast, the significant cumulative abnormal returns based on corporate governance suggested that corporate governance significantly impacted on SEO announcement returns in Nigeria. These findings suggest that policy makers should pay more attention to directors’ expertise, institutional ownership, board independence, and board size, as our results showed that investors might view them as dependable pointers of positive corporate information for the market, thus guaranteeing the best use of SEO proceeds.